Thymol Isolated from Thymus vulgaris L. Inhibits Colorectal Cancer Cell Growth and Metastasis by Suppressing the Wnt/β-Catenin Pathway - Zeng Q; Che Y; Zhang Y; Chen M; Guo Q; Zhang W (Dove Medical Press, 2020)
Qiongyao Zeng,1,2 Yuncheng Che,2 Yu Zhang,3 Mei Chen,2 Qiang Guo,1– 3 Wenjing Zhang2,4 1Faculty of Life Science and Biotechnology, Kunming University of Science and Technology, Kunming 650500, People’s Republic of China; 2Medical School, Kunming University of Science and Technology, Kunming 650500, People’s Republic of China; 3Department of Gastroenterology, The First People’s Hospital of Yunnan Province, Yunnan Provincial Institute of Digestive Medicine, Kunming 650032, People’s Republic of China; 4Department of Medical Oncology, The First People’s Hospital of Yunnan Province, Kunming 650032, People’s Republic of ChinaCorrespondence: Qiang GuoDepartment of Gastroenterology, The First People’s Hospital of Yunnan Province, No. 157 Jinbi Road, Kunming 650032, People’s Republic of ChinaTel +86-0871-63634031Email gqkj003@sina.comWenjing ZhangMedical School, Kunming University of Science and Technology, No. 727 South Jingming Road, Kunming 650500, People’s Republic of ChinaTel +86-0871-63638481Email wenjing_zhang1@163.comPurpose: Colorectal cancer (CRC) is one of the most commonly occurring cancers and is associated with high morbidity and mortality. Nevertheless, there is currently no safe and effective treatment for this condition. Thymol is a phenolic compound that is recognized as safe for use in food as well as medical and cosmetic fields. Increasing evidence has indicated that thymol exerts prominent antitumor effects in a variety of cancers, including CRC. However, how thymol elicits these effects on CRC and the associated underlying mechanisms remains unclear.Methods: HCT116 and Lovo cells were treated with different concentrations of thymol. Cell Counting Kit-8 (CCK-8) and transwell migration and invasion assays were used to evaluate cell proliferation, migration, and invasion, respectively. Cell apoptosis and cell cycle distribution were measured by flow cytometry. RT-qPCR, Western blot, and immunohistochemistry were used to detect the expression of related genes and their protein products.Results: In this study, we tested the antitumor activity of thymol extracted from a Chinese medicinal herb, Thymus vulgaris L. We show that thymol treatment in vitro inhibited cell proliferation and induced apoptosis and cell cycle arrest in CRC. Furthermore, in vivo treatment with 75 and 150 mg/kg thymol led to a significant decrease in tumor volume. Thymol administration induced CRC cell apoptosis through activation of the BAX/Bcl-2 signaling pathway. In addition, thymol suppressed CRC cell epithelial–mesenchymal transition (EMT), invasion, and metastasis via inhibiting the activation of the Wnt/β-catenin pathway, both in vitro and in vivo.Conclusion: Thymol may prevent CRC progression through inhibition of the Wnt/β-catenin signaling pathway, highlighting its potential as a novel therapeutic option for the treatment of CRC.Keywords: Wnt/β-catenin, colorectal cancer, thymol, tumor growth and metastasis